I have to rearrange the following, making p the subject of the equation: ln(p) = β0 + β1x I have got P = e^(β0 + β1x) Is this correct
Follow Math Help Forum on Facebook and Google+
Originally Posted by Orangeobe I have to rearrange the following, making p the subject of the equation: ln(p) = β0 + β1x I have got P = e^(β0 + β1x) Is this correct yes
Originally Posted by Jhevon yes Yes it is correct but you can use the rules of exponentials to say that then we get This assumes is a constant, if it is not constant than ignore this whole post
View Tag Cloud